Ecofeminist and Freedom Theology from Porong: a Study on Poetries Compilation by Children of Lapindo’s Victims - Mutiara Andalas (Yayasan Jurnal Perempuan, 2014)
This paper investigates poetries written by children victims of Lapindo narrating their suffering in speaking against the corporation and government’s indifferent. Those poetries exemplify and amplify the meaning of sisterhood among human being, ecology and its surrounding ecosystem in the tragic way. The children expose greediness as part of contemporary sin in connection to economic dimension. The aggression against women is similar with the aggression against the nature. This paper concludes that intellectus fidei will transform the practice of intellectus liberationem.